2021
DOI: 10.1007/978-3-030-80012-3_18
|View full text |Cite
|
Sign up to set email alerts
|

Visual Attention of Pedestrians in Traffic Scenes: A Crowdsourcing Experiment

Abstract: In a crowdsourced experiment, the effects of distance and type of the approaching vehicle, traffic density, and visual clutter on pedestrians' attention distribution were explored. 966 participants viewed 107 images of diverse traffic scenes for durations between 100 and 4000 ms. Participants' eye-gaze data were collected using the TurkEyes method. The method involved briefly showing codecharts after each image and asking the participants to type the code they saw last. The results indicate that automated vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…[ 54 ] Egocentric information transmitted by the eHMI, like “OK TO CROSS”, compelled pedestrians more than allocentric information like “STOPPING”. [ 55 ] Moreover, the reliability of eHMIs was questioned as it might be affected by weather, [ 56 ] light condition, [ 29 ] and vehicle behaviour. [ 35 ] For example, in poor weather, pedestrians could not always read vehicle signs.…”
Section: Human Behaviour Studies On Interactionsmentioning
confidence: 99%
“…[ 54 ] Egocentric information transmitted by the eHMI, like “OK TO CROSS”, compelled pedestrians more than allocentric information like “STOPPING”. [ 55 ] Moreover, the reliability of eHMIs was questioned as it might be affected by weather, [ 56 ] light condition, [ 29 ] and vehicle behaviour. [ 35 ] For example, in poor weather, pedestrians could not always read vehicle signs.…”
Section: Human Behaviour Studies On Interactionsmentioning
confidence: 99%
“…The implementation of AVs and the associated investigation of the interaction between AVs and other road users enlarge the application of multi-agent simulation. Bazilinskyy, Kooijman, Dodou, and de Winter [26] analyzed the interaction between an AV communicating via an eHMI, a human driver, and a pedestrian at a T-intersection with a zebra-crossing. The authors concluded that the multi-agent simulation is a promising tool to research interaction in traffic in the future.…”
Section: Previous Studies On Multi-agent Simulationmentioning
confidence: 99%
“…The visual behavior of pedestrians in a street crossing situation is influenced by the concrete layout of the street [13,41], but also to a large extent by the existence of the time pressure [48,2]. Due to its importance to traffic safety, pedestrian attention has been studied extensively in human science [2,14,20,61]. Automatic prediction of pedestrian attention can open up the possibility to create more realistic training environments both for humans and Figure 1.…”
Section: Introductionmentioning
confidence: 99%